2020
DOI: 10.1021/acs.biomac.0c00679
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric G-Quadruplex-Based CpG Oligodeoxynucleotides as Potent Toll-Like Receptor 9 Agonists

Abstract: Synthetic oligodeoxynucleotides (ODNs) containing unmethylated cytosine–phosphate–guanine (CpG) motifs trigger the immune response by stimulating endosomal Toll-like receptor (TLR) 9. Natural linear ODNs are susceptible to nuclease degradation, thereby limiting their clinical applications. Here, we designed monomeric G-quadruplex-based CpG ODNs (G4 CpG ODNs) containing CpG motifs in the central loop region of the G4 structure. The monomeric G4 CpG ODNs were more stable in serum than the linear ODNs. The monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(59 citation statements)
references
References 41 publications
(102 reference statements)
2
51
0
Order By: Relevance
“…To measure the CD spectrum, 2 µM CpG ODNs were dispensed into a 1-cm path length quartz cuvette (model T-18-ES-10, 1 cm path length, JASCO) and analyzed using a JASCO J-1500 spectropolarimeter at a scan speed of 50 nm/min, response time of 2.0 s, bandwidth of 1.0 nm, resolution of 0.2 nm, and sensitivity of 100 millidegrees (mdeg). CD spectra were recorded as the average of five replications over the spectral range of The CD melting experiments were performed from 5 • C to 90 • C with a temperature gradient of 1 • C/min based on the measurement of absorbance at 295 nm, as previously reported [9]. The Tm value was calculated by determining the upper and lower baseline values [18].…”
Section: Measurementmentioning
confidence: 99%
See 3 more Smart Citations
“…To measure the CD spectrum, 2 µM CpG ODNs were dispensed into a 1-cm path length quartz cuvette (model T-18-ES-10, 1 cm path length, JASCO) and analyzed using a JASCO J-1500 spectropolarimeter at a scan speed of 50 nm/min, response time of 2.0 s, bandwidth of 1.0 nm, resolution of 0.2 nm, and sensitivity of 100 millidegrees (mdeg). CD spectra were recorded as the average of five replications over the spectral range of The CD melting experiments were performed from 5 • C to 90 • C with a temperature gradient of 1 • C/min based on the measurement of absorbance at 295 nm, as previously reported [9]. The Tm value was calculated by determining the upper and lower baseline values [18].…”
Section: Measurementmentioning
confidence: 99%
“…These results indicated that the insertion of the CpG motif in the first and third loops preserved the antiparallel topology, whereas CpG ODNs with additional CpG motifs in the second loop failed to maintain the antiparallel topology. Next, we evaluated the immunostimulatory activity of G4-based CpG ODNs by examining mRNA expression in mouse macrophage-like RAW264 cells, since the transcript levels of inflammatory cytokine and type I interferon induced by CpG ODNs show the same tendency as protein secretion levels of these factors [9,19,20]. As shown in Figure 3, the position of the CpG motifs influenced cytokine production.…”
Section: Effect Of Cpg Motif Position In Anti-parallel Duplex/g4 Odns On G4 Formation and Immunostimulant Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…259,315 Besides the potential role of DNA G-quadruplexes in the telomeric repeats, their function is discussed in basically all contexts that are related to genomic DNA. 247,251,259,315 This includes in particular replication [316][317][318][319] , epigenetic processes such as CpG methylation 255,[320][321][322][323] or alterations to the chromatin structure 257,258,294 , genomic instability 96,253 and transcription 324,325 . Within the following chapters, the focus will be on DNA G4s as transcription regulatory elements.…”
Section: Occurence Of G-quadruplex Forming Sequences In the Human Genomementioning
confidence: 99%